Application of graph rewriting to natural language processing - Bonfante, Guillaume; Guillaume, Bruno; Perrier, Guy, 1950- (London : ISTE Ltd. ; Hoboken, NJ : John Wiley & Sons, Inc., 2018)
The paradigm of Graph Rewriting is used very little in the field of Natural Language Processing. But graphs are a natural way of representing the deep syntax and the semantics of natural languages. Deep syntax is an abstraction of syntactic dependencies towards semantics in the form of graphs and there is a compact way of representing the semantics in an underspecified logical framework also with graphs. Then, Graph Rewriting reconciles efficiency with linguistic readability for producing representations at some linguistic level by transformation of a neighbor level: from raw text to surface syntax, from surface syntax to deep syntax, from deep syntax to underspecified logical semantics and conversely.
5. Application of Graph Rewriting to Semantic Annotation in a Corpus5.1. Main stages in the transformation process; 5.1.1. Uniformization of deep syntax; 5.1.2. Determination of nodes in the semantic graph; 5.1.3. Central arguments of predicates; 5.1.4. Non-core arguments of predicates; 5.1.5. Final cleaning; 5.2. Limitations of the current system; 5.3. Lessons in good practice; 5.3.1. Decomposing packages; 5.3.2. Ordering packages; 5.4. The DSQ_to_DMRS conversion system; 5.4.1. Modifiers; 5.4.2. Determiners; 6. Parsing Using Graph Rewriting; 6.1. The Cocke-Kasami-Younger parsing strategy
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 20, 2018).
Keywords: Computational linguistics; Rewriting systems (Computer science); Graph theory -- Data processing; Language and logic; LANGUAGE ARTS & DISCIPLINES / Linguistics / Historical & Comparative; Computational linguistics; Graph theory -- Data processing; Language and logic; Rewriting systems (Computer science); Electronic books